The The Role of Islamic Economics in Achieving Sustainable Development Goals (SDGS): A Bibliometric Perspective - Jumiati, Eti (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: This study aims to explore the contribution of Islamic economics in supporting the achievement of Sustainable Development Goals (SDGs), especially SDGs 1 (no poverty), SDGs 4 (quality education), SDGs 10 (reducing inequality). Design/Method/Approach: Using bibliometric analysis methods, this study processes data from scientific publications between 2000 and 2023, obtained through Publish or Perish software and analyzed using VOSviewer. Findings: Key findings show that Islamic economics contributes significantly to supporting the achievement of the Sustainable Development Goals (SDGs), particularly in the aspects of poverty reduction, quality education, inequality reduction, and climate change mitigation. Islamic financial instruments such as zakat, cash waqf, and green sukuk, with examples of implementation such as Cash Waqf Linked Sukuk (CWLS) in Indonesia and green sukuk in Malaysia, have been effective in supporting economic, social, and environmental sustainability. Originality/Value: The implications of this study include strategic recommendations for policy makers and Islamic financial institutions in integrating Environmental, Social, and Governance (ESG) principles with Islamic instruments. This integration can strengthen the contribution of Islamic economics to inclusive and sustainable global development